2004
DOI: 10.1002/art.20568
|View full text |Cite
|
Sign up to set email alerts
|

Combination of infliximab and methotrexate therapy for early rheumatoid arthritis: A randomized, controlled trial

Abstract: Objective. To compare the benefits of initiating treatment with methotrexate (MTX) and infliximab (anti-tumor necrosis factor ␣ [anti-TNF␣] monoclonalantibody) with those of MTX treatment alone in patients with rheumatoid arthritis (RA) of <3 years' duration.Methods. RA patients were eligible if they had active disease and no prior treatment with MTX or a TNF␣ inhibitor. One thousand forty-nine patients were randomly assigned in a 4:5:5 ratio to 3 treatment groups: MTX-placebo, MTX-3 mg/kg infliximab, and MTX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
505
4
37

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,073 publications
(587 citation statements)
references
References 31 publications
41
505
4
37
Order By: Relevance
“…Details of the design of ASPIRE have been reported previously (19). Briefly, patients who were methotrexate (MTX) naive, had active RA, and had a history of persistent synovitis (for at least 3 months but no longer than 3 years from the date of diagnosis) began receiving MTX therapy with rapid dose escalation to 20 mg/week and were randomly assigned in a 5:5:4 ratio to receive either infliximab 3 mg/kg, infliximab 6 mg/kg, or placebo infusions at weeks 0, 2, and 6 and then every 8 weeks through week 46.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the design of ASPIRE have been reported previously (19). Briefly, patients who were methotrexate (MTX) naive, had active RA, and had a history of persistent synovitis (for at least 3 months but no longer than 3 years from the date of diagnosis) began receiving MTX therapy with rapid dose escalation to 20 mg/week and were randomly assigned in a 5:5:4 ratio to receive either infliximab 3 mg/kg, infliximab 6 mg/kg, or placebo infusions at weeks 0, 2, and 6 and then every 8 weeks through week 46.…”
Section: Methodsmentioning
confidence: 99%
“…signs and symptoms of disease, slow the rate of radiographic progression, and improve functional capacity (13)(14)(15)(16)(17)(18)(19). Although biologic agents are expensive and thus increase the direct costs of RA, their inhibitory effects on joint destruction may reduce the need for joint surgery and ultimately offset at least some of the increased direct costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent clinical trials evaluated whether the combination of a DMARD and an anti-TNFα agent was superior to either agent alone [11,12] or compared an anti-TNF agent with placebo [13,14]. Emboldened by the positive results of these trials, investigators probed a window of opportunity by asking whether treating patients with an anti-TNF agent in early stages (less than 3 years) of disease could 'wipe out' the disease and provide long-lasting remissions [12,[15][16][17].…”
Section: Joint Inflammationmentioning
confidence: 99%
“…[4] Newer 'biologic' DMARDs (bDMARDs) have had a substantial impact on patient care. The effectiveness of tumor necrosis factor-(TNF-) inhibitors -infliximab, adalimumab and etanercept -has been established in randomised controlled trials (RCTs) [5][6][7][8][9][10][11][12] and confirmed in meta analyses. [13][14][15] More recently, bDMARDs with alternative mechanisms such as rituximab, tocilizumab, and abatacept, along with new TNF-inhibitors -certolizumab pegol and golimumab -have come to market.…”
Section: Introductionmentioning
confidence: 99%